Eksplorasi Peran Generasi Z dan Milenial dalam Akselerasi Ekonomi Hijau melalui Media Massa - Alya Syifa Nurfadilah; Dwi Wijayanti; Raisa Irwansyah; Sri Mulyeni (Jurnal Manajemen Kewirausahaan dan Teknologi, 2026)
In the increasingly growing digital era, mass media has a very significant role in shaping the mindsets, behaviors, and aspirations of the younger generation, especially Generation Z and Millennials. This research aims to explore the role of the young generation in accelerating the green economy through mass media. This article uses the qualitative method of literature study. The results of the study show that mass media, can be from traditional forms such as television and newspapers or digital such as social media and internet-based platforms, play a role as the main means in disseminating information about the concept of the green economy, Gen Z and Millennials have advantages in mastering digital technology, using social media, and advantages to make all digital content creativity to form activities and create a golden Indonesia 2045. It can be concluded that this study confirms that the abundance of information from the mass media will not automatically change the behavior of young people to be pro-environment if it is not supported by internal factors. A solid foundation of financial literacy and deep environmental awareness is needed so that the flow of information can be filtered wisely. This sustainable change in economic progress rejects the focus of viral content alone, but requires real collaboration between government regulations, transparency of industry players, and a consistent commitment from Generation Z and Millennials to transform digital discourse into concrete action.